English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i am trying to come up with a formula that i can use in excel to figure out how much i need to make per hour to afford my living expenses.

here is the equation i can figure out how to solve:
n = g - (g * .26)

what i get is:
n = g - g * .26
n/.26 = g - g
....ERROR

can you helpe me figure this out?

2007-02-01 07:52:12 · 7 answers · asked by sean_mchugh6 3 in Science & Mathematics Mathematics

THANK YOU VERY MUCH EVERYONE!

2007-02-01 08:10:02 · update #1

7 answers

ur getting an error coz ur doing it wrong...

n = g - (g * .26)
taking 'g' common
n = g (1-.26)
n = g(.74)
n/.74 = g

i hope u get it...!!

2007-02-01 08:06:22 · answer #1 · answered by nUssie.. 2 · 0 0

I am assuming that g is the cell you want to test your salary with...

The problem with your equation is you can not divide out the .26 that way. you have to divide out the entire right side... not just a part of it.

Also let's say g is cell "A1". In "A2" type "=A1-A1*.26". This will give you the answer you're looking for.

2007-02-01 09:00:30 · answer #2 · answered by Marvin Q 2 · 0 0

So you have n in terms of g, and you want to solve this equation for g? When you divided both sides by 0.26, you didn't divide both terms on the right by 0.26, which is why it's not working. Here's how to solve the equation of yours for g:

n = g - (g * 0.26)
n = g - g * 0.26

Factor out a "g" from the right to get:
n = g(1 - 0.26)
n = g(0.74)

so g = n / (0.74)

2007-02-01 08:07:44 · answer #3 · answered by Anonymous · 0 0

n = g - (g * 0.26)
n = (1 - 0.26) * g
n = 0.74 * g
g = n / 0.74

What you did wrong was doing the subtraction first. The correct evaluation order is: innermost parenthesis first; within them, power and roots, then multiplication/division, then addition/subtraction.

2007-02-01 08:20:11 · answer #4 · answered by jcastro 6 · 0 0

so let's see...

n=g-g*.26
n=(1-.26)*g
n=.74*g
n/.74=g

I'm not sure if this is the answer that you are looking for, but i hope it is...

2007-02-01 08:10:13 · answer #5 · answered by Dana 1 · 0 0

Write as n = g - 0.26g
Thus n = 0.74g or, if you prefer:-
g = n / 0.74

2007-02-01 08:30:21 · answer #6 · answered by Como 7 · 0 0

solving for n:
n=g-(g*.26)
n=g-.26g
n=.74g

2007-02-01 08:06:14 · answer #7 · answered by sangreal 4 · 0 0

fedest.com, questions and answers